Effective R-value approach to comprehend the essence of integrated opaque passive substrate properties. (December 2021) - Zingre, Kishor T.; Kumar, D.E.V.S. Kiran; Wan, Man Pun; Chao, Christopher Y.H.
Abstract: The concept of 'effective' thermal resistance could facilitate in-depth understanding of the impact of passive substrate properties such as surface radiative and thermo-physical (which are not directly measurable using instrumentations in terms of R -value). A simple to-use and concise single performance factor has been formulated in this study to comprehend the effective thermal resistance provided by the enhanced surface radiative and thermo-physical properties of passive envelope materials. The derived expression is validated against measurements in real residential apartments located in Singapore. The derived effective thermal resistance expression is function of solar radiative properties, thermo-physical properties and weather parameters, and hence contains much more information than the traditionally estimated R-value. The effective thermal resistance is found to be dynamic in behavior i.e., thermal resistance (or heat flow character) of the envelope material varies with transient weather conditions. Increasing roof surface radiative properties i.e., solar reflectance (from 0.1 to 0.8) alone has advantages during both daytime and nighttime with daily integrated-heat gain reduction by 60–68%. Whereas increasing the other thermo-physical properties of the envelope i.e., adding insulation or thermal mass (with a layer of phase change material-modified skim coat) has advantage only during daytime, but penalty during nighttime for the hot climates. The effect of increasing the solar reflectance by 0.7 for an insulated gray aluminum metal roof (with 20-mm polystyrene) is almost equivalent to effectively further adding 40-mm thick polystyrene. The application of proposed approach has been demonstrated by investigating the effect of passive envelope properties for different roof assemblies under four different climates. Using this approach, the accuracy of estimation of heat flux through roof, an indicator of the roof thermal efficiency, was found to have improved by up to 78%. Highlights: Analytical model to study in-depth dynamic variation in the R -value due to passive substrate properties. Generalized expression which is applicable to any envelope assembly and climatic conditions. The proposed method is validated against measurements on a real-scale building. Parametric study is performed to evaluate dynamic performance of substrates for different climatic regions.